Technical, Economical and Environmental Assessments of the Solar Photovoltaic Technology in Southeast Sulawesi, a Developing Province in Eastern Indonesia - Rachman, Aditya; Rianse, Usman; Musaruddin, Mustarum; Ornam, Kurniati (International Journal of Energy Economics and Policy, 2015)
The aim of this study is to assess the technical, economical and environmental aspects on the application of the solar energy technology in Southeast Sulawesi, a developing province in eastern part of Indonesia. Mathematical models of the solar radiation falling on a tilted surface, the Levelised Cost of Energy (LCOE), and the solar lifecycle greenhouse gas and land use equivalent are employed to perform the assessments under a scenario of 5 percent solar power contribution in the electricity generation mix. The result shows that the solar technology incorporated by tracking system generates the high annual energy generated. Under some technical and economical scenarios, it is possible for the technology to obtain lower energy costs than the solar Feed-in-Tariff and the electricity production costs from other sources. The solar power not only generates low carbon emission, but also requires less land use, relatively to the availability land in this province. Keywords: Solar energy; economy; technical JEL Classifications: C4; C5; O05; Q2; Q4